Coupling functionalized cobalt ferrite nanoparticle enrichment with online LC/MS/MS for top-down phosphoproteomics. Issue 6 (18th April 2017) - Chen, Bifan; Hwang, Leekyoung; Ochowicz, William; Lin, Ziqing; Guardado-Alvarez, Tania M.; Cai, Wenxuan; Xiu, Lichen; Dani, Kunal; Colah, Cyrus; Jin, Song; Ge, Ying
Abstract : An integrated top-down phosphoproteomics strategy enabled by functionalized cobalt ferrite nanoparticle enrichment and online LC/MS/MS for identification, quantification, and characterization of low abundance phosphoproteins is presented. Abstract : Phosphorylation plays pivotal roles in cellular processes and dysregulated phosphorylation is considered as an underlying mechanism in many human diseases. Top-down mass spectrometry (MS) analyzes intact proteins and provides a comprehensive analysis of protein phosphorylation. However, top-down MS-based phosphoproteomics is challenging due to the difficulty in enriching low abundance intact phosphoproteins as well as separating and detecting the enriched phosphoproteins from complex mixtures. Herein, we have designed and synthesized the next generation functionalized superparamagnetic cobalt ferrite (CoFe2 O4 ) nanoparticles (NPs), and have further developed a top-down phosphoproteomics strategy coupling phosphoprotein enrichment enabled by the functionalized CoFe2 O4 NPs with online liquid chromatography (LC)/MS/MS for comprehensive characterization of phosphoproteins. We have demonstrated the highly specific enrichment of a minimal amount of spike-in β-casein from a complex tissue lysate as well as effective separation and quantification of its phosphorylated genetic variants. More importantly, this integrated top-down phosphoproteomics strategy allows for enrichment, identification, quantification, and comprehensive characterization of low abundance endogenous phosphoproteins from complex tissue extracts on a chromatographic time scale.